Temporary Weapons: Employers' Use of Temps against Organized Labor. (January 2014) - Hatton, Erin
Since the 1970s, U.S. employers have restructured their relationship to the labor market. This restructuring has included their rising use of nonstandard workers, particularly agency temps, and their systematic attacks on labor unions. These two trends are generally understood to be related but separate facets of a broader restructuring of the employment relationship. In this article, the author shows where and how these trends intersect by analyzing 106 labormanagement disputes. Employers use temps as weapons against unions in four primary ways: to prevent unions from forming, to weaken existing unions, to apply pressure on unions during negotiations, and to intimidate or harass striking workers. The author concludes that deploying agency temps in this way is a qualitatively new phenomenon—not simply a continuation of employers' longstanding practice of replacing union workers with "scab" labor.